Needs and assets of a public adult learning centre for the visually impaired : an educational study of Bosele - Sekgobela, Elias Mathea (My University, 2014)
This research is about establishing the needs and assets of a public adult learning centre for the visually impaired. The research is important because South Africa, as a signatory to the Salamanca Statement on Principles and Practice in Special Needs Education (UNESCO, 1994) and the Convention on the Rights of Persons with Disabilities in 2006 (Väyrynen, 2008), has an obligation to ensure the provision of quality education and training through inclusion. This also includes adult learners. The research emanated from the assumption that Public Adult Learning Centres for the Visually Impaired are not well equipped to provide quality education as envisaged by the Salamanca Statement and the Convention on the Rights of Persons with Disabilities. In order to resolve this assumption, a qualitative case study with Bosele Public Adult Learning Centre (BPALC) for the Visually Impaired was designed. The research participants from this centre were purposely sampled due to the importance of their shared experiences and opinions in answering the research question. Multiple perspectives were applied in data collection by means of semi-structured and focus group interviews and documents were examined and analysed to obtain in-depth information about the research. The analysis of the participants’ shared experiences and opinions, combined with observation and data analysis, assisted in deriving at the conclusion that, although Bosele is a Public Adult Learning Centre for the visually impaired, it is still deficient in terms of the capacity to provide quality education as envisaged in the Salamanca Statement and the Convention on the Rights of Persons with Disabilities. The learning and teaching support materials are inadequate and have not been modified for many years. The facilitators do not receive the necessary professional support and as such are inadequately prepared to provide quality education to the visually impaired adult learners. The available assets within and outside BPALC are not mapped and therefore not recognized for effective utilization. The teaching, learning and physical environment around BPALC is not conducive to the promotion of quality education for visually impaired adults. iii To respond to the findings of this research, several recommendations have been suggested and an empowerment programme has also been provided with a view to improve the quality of teaching and learning at BPALC. Suggestions for future research topics have also been made in order to close the gap that exists in research for the education of learners with visual impairment.
Thesis (M.Ed. (Community and Continuing Education)) -- University of Limpopo, 2014
Keywords: Adult education; Visually impaired; 371.90475; Special education -- South Africa; People with visual disabilities.; Adult education -- South Africa; Inclusive education